Epithelial-mesenchymal transition: An emerging target in tissue fibrosis - Li, Meirong; Luan, Fuxin; Zhao, Yali; Hao, Haojie; Zhou, Yong; Han, Weidong; Fu, Xiaobing (Experimental biology and medicine (Maywood, N.J.), 2016)
Epithelial-mesenchymal transition (EMT) is involved in a variety of tissue fibroses. Fibroblasts/myofibroblasts derived from epithelial cells contribute to the excessive accumulation of fibrous connective tissue in damaged tissue, which can lead to permanent scarring or organ malfunction. Therefore, EMT-related fibrosis cannot be neglected. This review highlights the findings that demonstrate the EMT to be a direct contributor to the fibroblast/myofibroblast population in the development of tissue fibrosis and helps to elucidate EMT-related anti-fibrotic strategies, which may enable the development of therapeutic interventions to suppress EMT and potentially reverse organ fibrosis.